Jan’s sense of humour – the smiling face of Jan Matejko - Kłak-Ambrożkiewicz, Marta (Laughter, humour, satire, 2024)
Jan Matejko (1838–1893) was above all a painter, and his artistic activity revolved around historical interests, a passion for research, the exploration of relics of the past, and their preservation from destruction. He developed these interests in parallel with his talent. He travelled extensively, visited museums and monuments, conducted in-depth historical and ethnographic studies. There was another Matejko – a man full of emotions, reflections, a sense of humour, self-irony, and distance. In his work, he did not shy away from allusive and often piquant pieces related to Poland’s past. The work presents Matejko’s works as well as occasional satirical drawings, which portray Matejko as a humorous and self-reflective individual. The artist’s character is illuminated through preserved satirical works, epistolary sources, memoirs, and a journal kept by Matejko’s secretary.